2020
DOI: 10.25273/counsellia.v10i2.7768
|View full text |Cite
|
Sign up to set email alerts
|

Teacher professional quality: Counselling services with technology in Pandemic Covid-19

Abstract: The Covid-19 pandemic is affecting academic processes around the world and the emergence of problems in students. School counsellors have a significant role in helping problems and developing student potential through counselling services with digital technology media. This study focuses on discovering various technologies that were applied and used by school counsellors in the process of counselling services during the Covid-19 pandemic. The research method used a case study method, and a qualitative descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 36 publications
(32 reference statements)
0
77
0
14
Order By: Relevance
“…It is helpful for the quality inspection process and carried out individualised tests of the patient. The significant benefits of these technologies are to improve patient satisfaction by changing the way of the traditional treatment system [ 38 , 39 ].…”
Section: Digital Dentistry Using Dentistry 40 Technologiesmentioning
confidence: 99%
“…It is helpful for the quality inspection process and carried out individualised tests of the patient. The significant benefits of these technologies are to improve patient satisfaction by changing the way of the traditional treatment system [ 38 , 39 ].…”
Section: Digital Dentistry Using Dentistry 40 Technologiesmentioning
confidence: 99%
“…The use of psychometrics and conducting risk assessments online has also shown encouraging results, though the need for further exploration is noted (Yates et al., 2017). A recent study with students showed technology‐based synchronous media (e.g., Facebook, WhatsApp) was the leading alternative for counselling during the pandemic (Supriyanton et al., 2020), and there are positive benefits of online therapy with some problematic behaviour, suggesting its potential as a medium for assessment and therapeutic services (Bortolon, et al., 2017; Toneatto et al., 2017). Yet, guidance about other formats of therapeutic interventions (e.g., physically distanced walk and talks, ecotherapy or animal therapy), has been lacking in communications to those who could provide such alternatives.…”
Section: Information Misinformation and Online Therapy Guidance In Tmentioning
confidence: 99%
“…Aplikasi teknologi memainkan peran penting dalam memfasilitasi pembelajaran berbasis digital (Syawaludin et al, 2019(Syawaludin et al, , 2020. Google Form adalah salah satu pemanfaatan teknologi dalam pembelajaran berupa template formulir atau lembar kerja yang dapat dimanfaatkan secara mandiri ataupun bersama-sama untuk tujuan mendapatkan informasi pengguna (Anugrahana, 2020;Fauzi, 2014;Mardiana & Purnanto, 2017;Ramadhani et al, 2019;Supriyanto et al, 2020). Aplikasi ini bekerja di dalam penyimpanan awan Google Drive bersama aplikasi lainnya seperti Google Sheet, Google Docs, dan pengayaan lainnya.…”
Section: Pendahuluanunclassified